From Tree Planting to Tree Growing: Rethinking Ecosystem Restoration Through Tree - Duguma, L.A.; Minang, Peter A.; Aynekulu, B. E.; Carsan, S.; Nzyoka, J.; Bah, A.; Jamnadass, Ramni H. (World Agroforestry Centre, 2020)
Every year, millions of dollars are spent on tree-based landscape restoration activities. Over the last five decades, there are few success stories of such interventions and even those do not match the anticipated objectives for which the resources were spent. News articles that announce planting campaigns of millions of seedlings are common. Despite all this, in many countries, vegetation cover has not improved due to poor seedling survival rate. This makes the return on investment low. The objective of this paper is to highlight the main underlying challenges that need to be tackled to make restoration through tree-based interventions successful. Numerous challenges hamper the success of project-supported public tree growing schemes. 1) Often tree planting is stated as the ultimate objective of the intervention; when that objective should instead be tree growing. Performance indicators are often the number of trees planted or area planted, not the number of trees grown, or the area of land covered with grown trees. 2) Most projects operate on a short time frame (1-3 years) while many tree species (e.g. native trees in many African countries) need more time to sufficiently grow. 3) Emphasis on the right trees, for the right place and the right purposes, is very weak. 4) Even in projects of adequate duration emphasis on after-planting management is often limited. 5) There is lack of tree tenure to formally transfer the management of planted trees to local communities who reside in the landscapes over a long period of time. Tackling these challenges and changing mindsets is crucial if restoration through tree-based interventions is to yield the intended outcomes of reversing ecosystem degradation.